Implementation of A Manuscript Management System for Small & Mid-sized Publishers - Liliani Priestiwanty; Rusdianto Roestam (IT for Society, 2021)
This research aims to fulfill the requirements of a management system for smaller trade publishers. An array of front end tools and backend in the form of sql database are used in the development. The system is done on a web-based platform and will handle the problem stated by delving into status-based categorization where each manuscript will be classified according to its state of status. These statuses are determined by a chain of subsequent validations. Scheduling itself is flexible and can even concur at the same time for manuscripts. The production processes are examined with a progress bar and with the addition of notification system will assure data passing is contained and could stay on schedule. Tests are conducted to confirm the system meets the conditions specified.